Quantum kinetics in transport and optics of semiconductors. (2nd, substantially rev. ed.) - Haug, Hartmut (Springer, 2017)
Introduction to Kinetics and Many-Body Theory -- Nonequilibrium Many-Body Theory -- Quantum Transport in Semiconductors -- Theory of Ultrafast Kinetics in Laser-Excited Semiconductors